Obesity and socioeconomic disadvantage in midlife female public sector employees: a cohort study - Aapo Hiilamo; Tea Lallukka; Minna Mänty; Anne Kouvonen (BMC, 2017)
Abstract Background The two-way relationship between obesity and socioeconomic disadvantage is well established but previous studies on social and economic consequences of obesity have primarily focused on relatively young study populations. We examined whether obesity is associated with socioeconomic disadvantage through the 10-12-year follow-up, and how obesity-related socioeconomic inequalities develop during midlife among women. Methods Baseline data were derived from the female population of the Helsinki Health Study cohort, comprising 40-60 -year-old employees of the City of Helsinki, Finland in 2000-2002 (n = 6913, response rate 69%). The follow-up surveys were carried out in 2007 (n = 5810) and 2012 (n = 5400). Socioeconomic disadvantage was measured by five dichotomous measures. Repeated logistic regression analyses utilising generalized estimating equations (GEE) were used to test the association between baseline self-reported obesity and the likelihood of socioeconomic disadvantage through all phases. The effect of time on the development of inequalities was examined by time interaction terms in random effect logistic regression models. Results After adjustment for educational level, baseline obesity was associated with repeated poverty (OR = 1.23; 95% CI; 1.05-1.44), frequent economic difficulties (OR = 1.74; 95% CI; 1.52-1.99), low household net income (OR = 1.23; 95% CI; 1.07-1.41), low household wealth (OR = 1.90; 95% CI; 1.59-2.26) and low personal income (OR = 1.22; 95% CI; 1.03-1.44). The differences in poverty rate and low personal income between the participants with obesity and participants with normal weight widened during the follow-up. Living without a partner and early exit from paid employment explained the widening of inequalities. Conclusions Weight status inequalities in socioeconomic disadvantage persisted or widened during the late adulthood.